Enhancing crop productivity and its economic farm profitabilty of smallholder farmer through the use of green manures from Alnus acuminata - Musana, B.; Nabahungu, N.L.; Bucagu, C.; Mukuralinda, A.; Barrios, E.; Rutebuka, J.; Nyaga, J; Muthuri, C. (Springer, 2024)
Decline in soil fertility is a major threat to land productivity and food security in the East African highlands. This calls for the application of nutrient inputs to improve crop productivity. A study was conducted in Nyabihu District of Rwanda from 2013 to 2016 to assess the effect of Alnus acuminata green manure (AGM)─applied in situ, through biomass alone, or combined with inorganic fertilizer─on the productivity and profitability of maize (Zea mays), beans (Phaseolus vulgaris), and potato (Solanum tuberosum). The treatments included application of AGM, inorganic fertilizer, combination of AGM and inorganic fertilizer, and unfertilized plot as a control (except for potato). These treatments were compared in two seasons and on two local soil fertility levels (medium and high) as defined by the farmer’s knowledge and experience. There was a convergence between farmers’ criteria and soil analysis in the soil fertility evaluation. Crops yields were analyzed using a linear mixed model while for other parameters, descriptive statistics were applied. The combination of AGM and inorganic fertilizer recorded the highest increment in maize (44%) and bean (46%) yields compared with inorganic fertilizer while it increased up to 87% compared with the unfertilized control. The financial analysis showed that AGM + inorganic fertilizer recorded the highest value-to-cost ratio (VCR) of 24.6 for potato and a significantly lower VCR (2.9) for maize and beans. The high VCR highlights a significant potential contribution of AGM + inorganic fertilizer to increase incomes of resource-constrained potato farmers in the Rwandan highlands. However, low crop prices possibly make this practice less attractive for those cultivating maize and beans.